Implementing the 5-Table Posyandu Model as an Intervention for Adolescent Anemia Prevention: An Experimental Study - Kaung Zaw; Putri Eka Sejati; Salsabilla Aprillita Riandi (Journal Of Nursing Practice, 2026)
Methods: Using a quasi-experimental one-group pretest-posttest design, 30 adolescent girls (aged 12–18) in the Sebulu I Health Centre work area were selected using purposive sampling. Knowledge was measured using questionnaires before and after the 5-table intervention. Results: The mean knowledge score significantly increased from 5.63 (pretest) to 11.83 (posttest). Respondents in the "Good" knowledge category surged from 10.0% to 60.0%. Statistical analysis using the Paired Samples Test yielded a p-value of 0.000 (p < 0.05), confirming a highly significant improvement. The systematic integration of screening and targeted education within the 5-table framework effectively bridged information gaps regarding the causes of anaemia, its symptoms, and iron supplementation. Conclusion: The implementation of the 5-table Posyandu Remaja framework significantly enhances adolescent girls' understanding of anaemia prevention. By combining systematic screening with targeted health education, this model serves as a strategic and scalable public health tool to mitigate the risk of anaemia among Indonesian adolescents.